High‐speed terrestrial substrate transitions: How a fleeing cursorial day gecko copes with compliance changes that are experienced in nature. (22nd November 2021) - Naylor, Emily R.; Higham, Timothy E.
Abstract: Animal movement is often largely determined by abiotic conditions of the environment, including substrate properties. While a large body of work has improved our understanding of how different substrate properties can impact locomotor performance and behaviour, few of these studies have investigated this relationship during transitions within a single locomotor event. In nature, terrestrial animals frequently encounter substrate transitions, or changes in substrate level, incline, texture and/or compliance during a single bout of movement, which can be sudden for high‐speed animals. These animals often adjust their posture and kinematics during transitions, and in some cases lose forward velocity. We examined the occurrence and effect of non‐elastic compliance transitions in Rhoptropus afer, a cursorial day gecko known for its ability to sprint rapidly for several metres at a time. We recorded substrate use during provoked escapes in the field and conducted locomotor trials on a trackway that mimicked natural structural habitat conditions with transitions from a rigid surface into sand and from sand back to a rigid surface. During escapes, R. afer used substrates of different compliance (i.e. rock, gravel and sand) and transitioned to and from the more compliant surfaces with even frequency, which matched substrate and compliance availability estimates. In laboratory experiments, sprint speed was not significantly affected by acute changes in compliance, which was likely facilitated by an increased body angle and duty factor upon entering the sand, and potentially a high yield strength of the sand relative to applied forces. We speculate that this species' ability to maintain speed during compliance transitions underlies their apparent indiscriminate substrate use during escapes, and that this behaviour may offer a selective advantage for evading larger terrestrial predators. Using field data to inform and contextualize laboratory experiments thus yields important insights as to how animals accommodate acute changes in substrate conditions encountered during critical locomotor events. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.